2013
DOI: 10.1097/bot.0b013e3182539333
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Pronator Quadratus Repair on Outcomes After Volar Plating of Distal Radius Fractures

Abstract: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
73
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 15 publications
(10 reference statements)
2
73
0
3
Order By: Relevance
“…The results of this study support the previous findings that dissection of the PQ muscle has minimal clinical impact on forearm rotation function 4,13,14). In a previous study that used isokinetic testing, Huh et al4) found that after loose repair of the PQ muscle after volar plating, both pronation and supination strengths were lower in the operated sides than in the normal sides at 6 months postoperatively; but at 1 year postoperatively, pronation strength was not significantly different and the decrease in pronation strength did not affect clinical outcomes.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of this study support the previous findings that dissection of the PQ muscle has minimal clinical impact on forearm rotation function 4,13,14). In a previous study that used isokinetic testing, Huh et al4) found that after loose repair of the PQ muscle after volar plating, both pronation and supination strengths were lower in the operated sides than in the normal sides at 6 months postoperatively; but at 1 year postoperatively, pronation strength was not significantly different and the decrease in pronation strength did not affect clinical outcomes.…”
Section: Discussionsupporting
confidence: 89%
“…On the contrary, Swigart et al9) found that there was no significant difference between the extent of PQ injury observed during the fracture fixation and clinical outcomes that included wrist motion and grip strength. In addition, studies reported outcomes that were not significantly different between injured and uninjured forearms or between PQ repair in patients with a DRF treated with volar plating 4,13,14). However, none of the studies have assessed the correlation between the actual anatomical healing status of PQ after volar plating and clinical outcomes.…”
mentioning
confidence: 99%
“…Concerning the latter study, results are not ambiguous. Hershman et al showed in contrast to the recommendation of Brown and Lifchez that there is no advantage in repairing the pronator quadratus during palmar plating of distal radius fractures [21,22]. No difference could be recognized concerning range of motion, grip strength or DASH and VAS score 1 year postoperatively if the pronator quadratus was refixed or not after palmar plating of the distal radius [23].…”
Section: Discussionmentioning
confidence: 98%
“…A recent clinical study examined the potential hazards of failing to repair the PQ after open volar approach. 17 This study did not find a clear outcome difference between patients in whom repair was attempted and patients in whom it was not. However, this is not the question examined by this biomechanical study, in which PQ excursion is limited.…”
mentioning
confidence: 43%